If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6x + 6.6 = 3.3 Reorder the terms: 6.6 + 0.6x = 3.3 Solving 6.6 + 0.6x = 3.3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6.6' to each side of the equation. 6.6 + -6.6 + 0.6x = 3.3 + -6.6 Combine like terms: 6.6 + -6.6 = 0.0 0.0 + 0.6x = 3.3 + -6.6 0.6x = 3.3 + -6.6 Combine like terms: 3.3 + -6.6 = -3.3 0.6x = -3.3 Divide each side by '0.6'. x = -5.5 Simplifying x = -5.5
| y^2-36y+64=0 | | m^3-121m=0 | | y=-0.80(25)+136 | | 14+2k-22=k | | -5y+4y+16=-56 | | 6+2(1x+-5)=2x+-4 | | .28x+3=0.14 | | 20y-5=3(y-47) | | -6x+9=20-4x | | -3x+3=x-25 | | 2[3-3(x+1)]+1=2(-15-x)+2x+15 | | 20-2=205 | | v-7+8=19 | | 3x-50+2x-5=180 | | 9a^3b^2+12ab^2=0 | | 85+4=99 | | 30*x/30= | | -0.6(5x)=90 | | 1.8+n=15.72 | | 7x-5=4x-41 | | 2x+3x-8=22 | | 3*x/30= | | 25-8=12.5 | | 3.6x=5.4+3.3x | | 9+2.7x=-4.8x-6 | | -5+3x=x-25 | | 4(x+10)=20 | | 15(8c-1)-8=118c+15 | | i^4-1=0 | | 2x+15=3x-10 | | -0.75-3x=-9 | | 11x+5x=18 |